The Mr. & Mrs. Joseph Randall Shapiro Collection. - Wood, James N.; Randall Shapiro, Joseph; Kuh, Katharine (Chicago : The Art Institute of Chicago, 1985)
Bacon, Francis ; Baj, Enrico ; Balthus ; Baziotes, William ; Bellmer, Hans ; Brauner, Victor ; Chagall, Marc ; Cornell, Joseph ; Dali, Salvador ; Delvaux, Paul ; Derain, Andre ; Dubuffet, Jean ; Ernst, Max ; Giacometti, Alberto ; Grosz, George ; Klee, Paul ; Man Ray ; Moore, Henry ; etc.
The Mr. & Mrs. Joseph Randall Shapiro Collection, The Art Institute of Chicago, February 23 - April 14, 1985
kunstcatalogus